Codex Sinaiticus a facsimile edition (Peabody Hendrickson, 2010)
Codex Sinaiticus is one of the world’s most remarkable books. Written in Greek in the fourth century, it is the oldest surviving complete New Testament, and one of the two oldest manuscripts of the whole Bible. No other early manuscript of the Christian Bible has been so extensively corrected, and the significance of Codex Sinaiticus for the reconstruction of the Christian Bible’s original text, the history of the Bible and the history of western book making is immense. Since 2002, a major international project has been creating an electronic version of the manuscript. This magnificent printed facsimile reunites the text, now divided between the British Library, the National Library of Russia, St Catherine’s Monastery, Mt Sinai and Leipzig University Library.
Keywords: 091:22 -- Bijbels--(handschriften)